Follow the yellow flag road : advancing the biological control of a global wetland invader, and a case study on ecosystem recovery - Minuti, Gianmarco (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Global change is accelerating habitat degradation and extinction rates, disproportionately affecting freshwater ecosystems. Biological invasions, a core component of global change, have been recognized as a major driver of this phenomenon. Invasive alien aquatic plants (IAAPs) are a prime example, disrupting ecological dynamics and hindering the economic and social activities that depend upon freshwater ecosystems. The best approach to managing IAAPs is preventing their introduction and taking swift action when infestations are detected. Unfortunately, most IAAPs are only recognized after they have spread, making eradication difficult and requiring expensive, ongoing management through manual, mechanical, or chemical means, which become less effective as infestations grow. In this regard, a sustainable alternative against IAAPs is provided by classical biological control. This method lays on the assumption that invasive species have been introduced in an environment which is free from their natural enemies, and that such release allowed them to redirect their resources towards growth and reproduction. Accordingly, weed biocontrol involves introducing one such enemy - a so-called biocontrol agent - to regulate the population of the plant, ideally reducing its density below a critical threshold, minimizing its impacts. Biocontrol programs must follow stringent protocols in order to a) ensure the selection of the most appropriate agents; b) guarantee their establishment and effectiveness in controlling their target; c) minimize the risks involved with their release; and d) monitor their impacts after they have been released. This thesis is composed of two parts, focusing on pre-release studies (Part I, Chapters 1-4) and post-release evaluations (Part II, Chapter 5), respectively. Part I explores the biological control of Iris pseudacorus L. (Iridaceae) "“ yellow flag "“ a Eurasian plant that has invaded temperate wetlands worldwide. The first step consisted of conducting field surveys across the native range of the weed, which led to the selection of three candidate biocontrol agents. As a second step, bioclimatic niche modelling was used to forecast the current and future suitability of the weed and its prospective agents. These models helped to identify areas most at risk of invasion and predict how climate change might affect biocontrol efficacy, showing differing impacts in the Northern and Southern Hemispheres. Further, a scoring system was developed to prioritize non-target plants for host-specificity testing, focusing on species within the family Iridaceae. Most taxa prioritized are native to the Americas, South Africa and eastern Asia, highlighting the importance of collaboration across regions when dealing with global invaders with complex phylogeographic distributions. Finally, a germination study confirmed that I. pseudacorus seeds from Argentina germinate more than Belgian seeds, especially in absence of cold stratification, suggesting increased performances of invasive populations and an adaptation to warmer temperatures. Nonetheless, impact assessments conducted on one of the three biocontrol agents demonstrated that it could cause juvenile mortality, suggesting it may effectively reduce seedling recruitment, though further research on agents targeting reproductive structures is recommended. Part II of the thesis addresses an often understudied aspect of post-release evaluations: ecosystem recovery following biological control. To do so, a case study is presented, investigating the biological control of water fern, Azolla filiculoides Lamb. (Salviniaceae), in Belgium. The results of this study are used to discuss the shortcomings of different experimental designs, the lack of baseline data in invasion ecology, and the intricacies of defining and quantifying ecosystem recovery in light of legacy effects and context-dependency.,Wereldwijde verandering versnelt de degradatie van habitats en de uitstervingscijfers, met een onevenredige impact op zoetwaterecosystemen. Biologische invasies, een kernonderdeel van klimaatverandering, worden erkend als een belangrijke drijvende kracht achter dit fenomeen. Invasieve uitheemse waterplanten (IAAPs) zijn een duidelijk voorbeeld, omdat ze ecologische dynamiek verstoren en economische en sociale activiteiten belemmeren die afhankelijk zijn van zoetwaterecosystemen. De beste aanpak voor het beheer van IAAPs is het voorkomen van hun introductie en het nemen van snelle maatregelen bij het detecteren van besmettingen. Helaas worden de meeste IAAPs pas herkend nadat ze zich hebben verspreid, wat uitroeiing moeilijk maakt en dure, voortdurende beheersing vereist door handmatige, mechanische of chemische middelen, die minder effectief worden naarmate besmettingen toenemen. In dit opzicht biedt klassieke biologische bestrijding een duurzaam alternatief tegen IAAPs. Deze methode berust op de veronderstelling dat invasieve soorten zijn geïntroduceerd in een omgeving die vrij is van hun natuurlijke vijanden, waardoor ze hun middelen konden richten op groei en reproductie. Bijgevolg omvat onkruidbestrijding het introduceren van een dergelijke vijand - een zogenaamde biocontrole-agent - om de populatie van de plant te reguleren, idealiter door de dichtheid ervan onder een kritische drempel te verlagen en zo de impact ervan te minimaliseren. Biocontroleprogramma's moeten strikte protocollen volgen om a) de selectie van de meest geschikte agens te waarborgen; b) hun vestiging en effectiviteit bij het beheersen van hun doel te garanderen; c) de risico's van hun vrijlating te minimaliseren; en d) hun impact na vrijlating te monitoren. Dit proefschrift bestaat uit twee delen, gericht op respectievelijk pre-release studies (Deel I, Hoofdstukken 1-4) en post-release evaluaties (Deel II, Hoofdstuk 5). Deel I onderzoekt de biologische bestrijding van Iris pseudacorus L. (Iridaceae) - gele lis - een Euraziatische plant die gematigde moeraslanden wereldwijd heeft gekoloniseerd. De eerste stap bestond uit het uitvoeren van veldonderzoeken in het inheemse verspreidingsgebied van het onkruid, wat leidde tot de selectie van drie kandidaat-biocontroleagenten. Als tweede stap werd bioklimatisch nis-modelleren gebruikt om de huidige en toekomstige geschiktheid van het onkruid en zijn potentiële agens te voorspellen. Deze modellen hielpen gebieden met het grootste risico op invasie te identificeren en voorspelden hoe klimaatverandering de effectiviteit van biocontrole zou kunnen beïnvloeden, met verschillende effecten op het noordelijk en zuidelijk halfrond. Daarnaast werd een scoresysteem ontwikkeld om niet-doelplanten te prioriteren voor host-specifieke tests, met de nadruk op soorten binnen de familie Iridaceae. De prioritaire taxa zijn inheems in Amerika, Zuid-Afrika en Oost-Azië, wat het belang van samenwerking tussen regio's onderstreept bij het omgaan met mondiale invasieve soorten met complexe fylogeografische verspreiding. Ten slotte bevestigde een kiemingsstudie dat I. pseudacorus zaden uit Argentinië meer kiemen dan Belgische zaden, vooral bij afwezigheid van koude stratificatie, wat wijst op verhoogde prestaties van invasieve populaties en aanpassing aan warmere temperaturen. Nochtans toonden effectbeoordelingen van een van de drie biocontroleagens aan dat deze de mortaliteit van juvenielen kon veroorzaken, wat suggereert dat het effectief kan zijn bij het verminderen van de zaailingrekrutering. Toch wordt verder onderzoek naar agenten die zich richten op reproductieve structuren aanbevolen. Deel II van het proefschrift behandelt een vaak onderbelicht aspect van post-release evaluaties: ecosysteemherstel na biologische bestrijding. Om dit te realiseren wordt een casestudy aangeboden over de biologische bestrijding van watervaren, Azolla filiculoides Lamb. (Salviniaceae), in België. De resultaten van deze studie worden gebruikt voor de bespreking van de tekortkomingen van verschillende experimentele ontwerpen, het gebrek aan basisgegevens in invasie-ecologie en de complexiteit van het definiëren en kwantificeren van ecosysteemherstel in het licht van nalatenschapseffecten en contextafhankelijkheid.
Keywords: Aquatic plants; Invasive plants -- Biological control; Iris pseudacorus; Azolla filiculoides; Aphthona nonstriata; Host specificity